Contrast-enhanced ultrasound (CEUS) in blunt abdominal trauma - Miele, Vittorio (Br J Radiol, 2016)
Baseline ultrasound is essential in the early assessment of patients with a huge haemoperitoneum undergoing an immediate abdominal surgery; nevertheless, even with a highly experienced operator, it is not sufficient to exclude parenchymal injuries. More recently, a new ultrasound technique using second generation contrast agents, named contrast-enhanced ultrasound (CEUS) has been developed. This technique allows all the vascular phase to be performed in real time, increasing ultrasound capability to detect parenchymal injuries, enhancing some qualitative findings, such as lesion extension, margins and its relationship with capsule and vessels. CEUS has been demonstrated to be almost as sensitive as contrast-enhanced CT in the detection of traumatic injuries in patients with low-energy isolated abdominal trauma, with levels of sensitivity and specificity up to 95%. Several studies demonstrated its ability to detect lesions occurring in the liver, spleen, pancreas and kidneys and also to recognize active bleeding as hyperechoic bands appearing as round or oval spots of variable size. Its role seems to be really relevant in paediatric patients, thus avoiding a routine exposure to ionizing radiation. Nevertheless, CEUS is strongly operator dependent, and it has some limitations, such as the cost of contrast media, lack of panoramicity, the difficulty to explore some deep regions and the poor ability to detect injuries to the urinary tract. On the other hand, it is timesaving, and it has several advantages, such as its portability, the safety of contrast agent, the lack to ionizing radiation exposure and therefore its repeatability, which allows follow-up of those traumas managed conservatively, especially in cases of fertile females and paediatric patients.